2021
DOI: 10.1002/pssa.202100614
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Injection and Annealing‐Enhanced Electrical Performance in Tunnel Oxide‐Passivated Contact Silicon Solar Cells

Abstract: Herein, it is demonstrated that low temperature current injection and annealing (CIA) treatment can cause evident improvements in open circuit voltage, short‐circuit current, and fill factor of tunnel oxide‐passivated contact (TOPCon) silicon solar cells, leading to a notable conversion efficiency gain (over 0.4% absolute at the best condition). The effects of injected current and annealing temperatures toward the improvement of electrical performance of the TOPCon solar cells are compared. The more evident in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The light soaking that is being widely used in SHJ solar cells can improve the surface passivation and reduce J 0c by reducing the density of interface states acting as the recombination center 205,206 . The current injection and annealing (CIA) and reverse bias annealing can effectively passivate the defects and reduce ρ c of c ‐Si solar cells by promoting the transport of interstitial hydrogen into the c ‐Si wafers 231 . The hydrogen passivation that has been achieved by different strategies in PERC, TOPCon, and SHJ technologies is also worth trying in dopant‐free passivating contacts, such as FGA treatment and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light soaking that is being widely used in SHJ solar cells can improve the surface passivation and reduce J 0c by reducing the density of interface states acting as the recombination center 205,206 . The current injection and annealing (CIA) and reverse bias annealing can effectively passivate the defects and reduce ρ c of c ‐Si solar cells by promoting the transport of interstitial hydrogen into the c ‐Si wafers 231 . The hydrogen passivation that has been achieved by different strategies in PERC, TOPCon, and SHJ technologies is also worth trying in dopant‐free passivating contacts, such as FGA treatment and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…205,206 The current injection and annealing (CIA) and reverse bias annealing can effectively passivate the defects and reduce ρ c of c-Si solar cells by promoting the transport of interstitial hydrogen into the c-Si wafers. 231 The hydrogen passivation that has been achieved by different strategies in PERC, TOPCon, and SHJ technologies is also worth trying in dopant-free passivating contacts, such as FGA treatment and so forth.…”
Section: 175mentioning
confidence: 99%
“…Besides, by measuring the change of J 0 during the carrier-induced hydrogenation treatment, they proposed that hydrogen is of significance in the enhanced Si/SiO x interface defects passivation. More recently, Hu et al [128] also reported the improved conversion efficiency of TOPCon solar cells by using current injection and annealing (CIA) treatment, as shown in figure 27, which could also be related to the enhanced hydrogenation of interface defects. For details, the change in the electrical properties of Si/SiO 2 interface after hydrogenation has been discussed in [129].…”
Section: Huge Benefits Of Hydrogenation On Next-generation Silicon So...mentioning
confidence: 98%